Measuring the performance of Dehyariha Foundation in terms of economic, social and environmental indicators in rural regions (Case study: Sarbisheh County) - Hassan Azizi Bohloli; Mahmoud Reza Anvari; Masoumeh Hafez Rezazadeh (تحقیقات کاربردی علوم جغرافیایی)
Rural management has always undergone various changes. Today, this pillar is the responsibility of the rural municipality Foundation. The purpose of forming this institution is to have a strong executive force in order to develop rural areas. rural municipality, as the executor of village programs and projects, has an important role in reducing urban and rural inequalities and improving the development of the village. Determining the degree of success of rural municipality in performing tasks is possible when its performance is carefully measured. The purpose of this study is to assess the performance of rural municipality Foundation in terms of economic, social and environmental indicators in rural areas of Sarbisheh. The research method is descriptive-analytical and based on data collection in the field through a questionnaire. The statistical population of the study consisted of heads of households (1931 households) in 30 villages with rural areas. The sample size at the level of heads of households was calculated using the Cochran's formula of 320 people. The result of one-sample t-test showed that the best performance of rural areas is significantly less than 0.05 in terms of social indicators with an average of 3.78. Also, a significant difference was observed between the studied villages in the field of social indicators with a significant level (0.008), economic indicators with a significant level equal to (0.004) and environmental-physical indicators with a significant level (0.047). In terms of social performance, Dehneh Chah village with an average of 4.43, in terms of economic and environmental performance, Baghestan village with an average of 3.90 and 4.16 are in first place. The study of paired t-test with a significance level of less than 0.05 and an average difference of (-1.271) indicates that the situation of rural development indicators has become more appropriate after the establishment of the rural municipality Foundation. Keywords: Dehyariha performance, economic, social and environmental indicators, rural areas, Sarbisheh.